Role of Neuro-Immune Cross-Talk in the Anti-obesity Effect of Electro-Acupuncture - Lu, Mengjiang; He, Yan; Gong, Meirong; Li, Qian; Tang, Qianqian; Wang, Xuan; Wang, Yaling; Yuan, Mengqian; Yu, Zhi; Xu, Bin (Frontiers in Neuroscience, 2020)
There is evidence to show that electro-acupuncture (EA) has a promotive effect on both lipolysis and thermogenesis, and that these mechanisms underlie the anti-obesity effect of EA. The sympathetic nervous system (SNS) is known to play a role in thermogenesis. Additionally, obesity is characterized by a chronic low-grade inflammatory state. Based on these findings, the aim of the present study is to investigate the potential neuro-immune mechanisms underlying the therapeutic effect of EA in obesity. In the experiment, we used high fat diet (HFD) rats model to study the effect of EA in reducing body weight. EA increases the activity of sympathetic nerves in iWAT, especially in the HFD group. Comparing to HFD rats, EA can decrease SAMs and the level of Slc6a2 protein. The relative UCP1 expression shows EA increase thermogenesis in iWAT, and also increases β3 receptors. Interesting, injecting β antagonist in iWAT increase Slc6a2 protein level. Additionally, the SNS-macrophage cross-talk response to EA showed in iWAT but not in eWAT. The results of the present study indicate that EA exerts its anti-obesity effect via three mechanisms: (1) inhibition of SAMs and the NE transport protein SlC6a2, (2)promoting SNS activity and thermogenesis, and (3) regulating immunologic balance.